An exploratory study on the role of occupational therapists in home-based rehabilitation team in South Korea - Young-Myoung Lim; Jae-Shin Lee; Su-Kyoung Kim; Tae-Hyun Cha; Doo-Han Yoo; Hee Kim (Hong Kong Journal of Occupational Therapy)
Introduction: Cooperation among rehabilitation team members is essential in the home-based rehabilitation setting. Q-methodology that can quantitatively analyze the subjectivity of members of the rehabilitation team was used to explore the role of occupational therapists (OTs) in home-based rehabilitation. Methods: The Q-methodology process was implemented in five steps: Step 1 - Representative statements about the role of OTs were collected through in-depth interviews, open questionnaires, and literature reviews (Q-sample); Step 2 - A total of 34 rehabilitation team members (physical therapists, OTs, social workers, nutritionists) were recruited (P-sample); Step 3 - The statements were classified according to their subjective perspective (Q-sort); Step 4 - Factor analysis was performed based on the correlation among the responses from the participants (Q-factor analysis); Step 5 - The awareness factor for roles was interpreted (Interpretation of awareness factors). Results: The roles of OTs perceived by members of the home-based rehabilitation team were formed into five factors (A) Adaptation within home environments; (B) Professional development; (C) Reliable service execution; (D) Client needs resolution; and (E) Focus on activity participation. In all factors, perspectives on the role of OTs in helping clients participate in their roles and activities at home were included. These factors included issues and directions addressed in prior literature on the development of occupational therapy. Conclusions: In home-based rehabilitation, OTs must play a professional role in ensuring clients live fully at home, and cooperate with team members for an effective rehabilitation approach.